Primordial germ cells of Astyanax altiparanae, isolated and recovered intact after vitrification: A preliminary study for potential cryopreservation of Neotropical fish germplasm - Rosero, Jenyffer; Pessoa, Giselle Pessanha [UNESP]; Carvalho, Gabriella Braga; López, Lucia Suárez; dos Santos, Silvio Carlos Alves; Bressan, Fabiana Fernandes; Yasui, George Shigueki (Elsevier, 2024)
Primordial germ cells (PGCs) constitute an important cell lineage that directly impacts genetic dissemination and species conservation through the creation of cryobanks. In order to advance the field of animal genetic cryopreservation, this work aimed to recover intact PGCs cryopreserved in embryonic tissues during the segmentation phase for subsequent in vitro maintenance, using the yellow-tailed tetra (Astyanax altiparanae) as a model organism. For this, a total of 202 embryos were distributed in two experiments. In the first experiment, embryos in the segmentation phase were dissociated, and isolated PGCs were maintained in vitro. They were visualized using gfp-Pm-ddx4 3′UTR labeling. The second experiment aimed to vitrify PGCs using 3 cryoprotective agents or CPAs (dimethyl sulfoxide, ethylene glycol, and 1,2 propanediol) at 3 molarities (2, 3, and 4 M). The toxicity, somatic cell viability, and recovery of intact PGCs were evaluated. After cryopreservation and thawing, 2 M ethylene glycol produced intact PGCs and somatic cells (44 ± 11.52 % and 42.35 ± 0.33 %, respectively) post-thaw. The recovery of PGCs from frozen embryonic tissues was not possible without the use of CPAs. Thus, the vitrification of PGCs from an important developmental model and Neotropical species such as A. altiparanae was achieved, and the process of isolating and maintaining PGCs in a culture medium was successful. Therefore, to ensure the maintenance of genetic diversity, PGCs obtained during embryonic development in the segmentation phase between 25 and 28 somites were stored through vitrification for future applications in the reconstitution of species through germinal chimerism.
Keywords: Cryobank; Cryoprotectant; Embryo; PGC; Yellow-tail tetra